Hubungan Penggunaan Smartphone dengan Aktivitas Olahraga pada Siswa SMP N 2 Kalikajar - Muhamad Andri Setyawan; Kurnia Wijayanti; Nopi Nur Khasanah (Journal of Health, Medical, and Psychological Studies, 2025)
Smartphone use among students has increased significantly alongside the rapid advancement of digital technology. High levels of smartphone use can shift physical activity toward sedentary behavior, thereby influencing students’ exercise habits and overall healthy lifestyle. The imbalance between high smartphone use and declining physical activity among adolescents has raised concerns about their health. Therefore, this study aims to examine the relationship between smartphone use and physical activity among students. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 59 respondents selected through a random sampling technique. Data were collected using a smartphone use questionnaire and a physical activity questionnaire. The relationship between variables was analyzed using the Spearman Rank correlation test. The analysis revealed a Spearman correlation coefficient of r = 0.281 with a significance value of p = 0.031 (p < 0.05), indicating a positive and significant relationship between smartphone use and physical activity, although the correlation strength is categorized as weak. The positive direction of the relationship suggests that productive smartphone use, such as through fitness applications, may help increase physical activity.